Length of survival of people living with HIV/AIDS in Guyana from 2003 to 2015 - Nero, Nicola Aliceen (2023)
Human immunodeficiency virus (HIV) is an infection that affects the body\'s immune system, specifically the white blood cells called CD4 count (WHO, 2022). As a global health concern, HIV/AIDS has been around for decades and to date, there is no known cure for the disease, however, with good health seeking behavirous, treatment, care and support, many persons affected are continuing to live long, comfortable and adoptable lives. Objective: The main objective of this study was to analyze the survival of people living with HIV and AIDS in Guyana from 2003 to 2015. Method: A retrospective cohort study was done of individuals with HIV/AIDS, notified and in care at seventeen (17) HIV Care and Treatment Sites, Ministry of Health, Guyana, from 2003 to 2015. The study took the form of a desk review of a cohort of individuals entered in the registry, consisting of clinical and treatment information that assisted to answer the proposed questions. Result: Of the 17 HIV Care and Treatment Sites assessed, the final bank produced a total of 1,067 (one thousand and sixty-seven patients) for analysis. Fifty six (56%) female and forty four 44% male. Eight variables were evaluated for this study that provided specific results as per analysis. Conclusion: Overall, patients with a high category of the CD4 variable have less risk of death and a good overall survival state and co-morbidities do contribute to an early death, especially if the ARV treatment regimen is not adhered to. Guyana\'s priority purposes are to reduce the transmission of HIV and improve the quality of life of persons living with HIV/AIDS. With great efforts and collaboration, several strategies are combined to improve access to adequate and high quality treatment care and support to all persons living with HIV/AIDS.